Regularidade de Soluções de Uma Classe de Problemas Elípticos Semi-lineares - Clemente, Rodrigo Genuino (2011)
We start studing semi-stable solutions for the equation u = f(u) in a smooth and bounded domain of Rn, 2 n 4. The presented result is a L1 boundedness, which holds for all semi-stable positive solution and all non-linearity f. We also show a approach about the case u = f(u) in the unitary ball of Rn. The results obtained are Lq and Wk;q estimates for semi-stable radial solutions u 2 H1 0 , the proof of a boundedness if n 9 and, in case that g is increasing and convex, u 2 W3;2 in all dimension n.